Institutional Strengthening of Electoral Commission in Increasing Voter Participation in Medan Mayoral Elections 2020 - Amin, Muryanto; Nasution, Muhammad Arifin; Nasution, Faiz Albar (Talenta Publisher, 2021)
Institutional strengthening of Electoral Commission is a model to increase voter participation in 2020 Medan Mayoral Elections. Purpose of activities in improving voter participation through; First, describe trend of voter participation in Medan. Second, explain the Readiness of the Medan Municipal Election Commission in 2020 Regional Head Elections. Third, explaining institutional strengthening of Electoral Commission in increasing voter participation in Medan. Method of implementation of activities through a panel discussion with Blended learning based on webinars, and face-to-face with Selection Committee of Medan District. Results of devotion show; First, trend voter participation in regional head elections tends to be low, so a social and cultural approach is needed in increasing participation in Medan. Second, readiness of Medan Municipal Election Commission in the 2020 regional elections is readiness of human resources, socialization, participation and adaptation of new normal life. Third, institutional strengthening of Electoral Commission in increasing voter participation should be done to Ad Hoc institutions such as District Election Committee, Voting Committee, Voter Data Update Officer and Voting Organizing Group to better understand duties, functions and protocols of health. In addition, new innovations in political socialization and political education through information technology media provide public awareness and increase voter participation